Integration of PJBL, STEAM, and Learning Tool Development in Improving Students' Critical Thinking Skills - Sri Dwi Indahwati; Fida Rachmadiarti; Eko Hariyono (IJORER : International Journal of Recent Educational Research, 2023)
Objective: This research aims to explore improving critical thinking skills by applying Project Based Learning (PjBL) based on the STEAM (Science, Technology, Engineering, Arts, and Mathematics) model in Renewable Energy material at 1st Trowulan State Vocational School. The main aim of this research is to assess the effectiveness of STEAM-based PjBL in improving students' critical thinking skills at 1st Trowulan State Vocational School Trowulan. Method: The research method used was an experiment with a One Group Pre-test and Post-test design. The research subjects comprised 25 students of Class X Computer and Network Engineering 1 (X-1) and 26 students of Class X Computer and Network Engineering 1 (X-2). During the research, students were given PjBL-based learning with a STEAM approach to Renewable Energy material. Before and after learning, students are tested using a pre-test and post-test to measure the increase in their critical thinking skills. Results: The analysis shows that implementing PjBL-based learning based on STEAM is efficacious in improving students' critical thinking abilities. A comparison of pre-test and post-test scores on Renewable Energy material shows a significant increase in students' critical thinking abilities. Novelty: The novelty of this research lies in its new contribution to the field of education. The combination of the PjBL and STEAM approaches in learning Renewable Energy makes a new contribution to preparing students to face real-world challenges that continue to develop. Critical thinking ability is an essential skill in facing the challenges of the 21st century, and this research shows that this approach is practical in developing it. Integrating critical thinking skills into STEAM-based learning provides essential added value in education.